CLASS, SERVITUDE, AND THE CRIMINAL JUSTICE SYSTEM IN EARLY VICTORIAN LONDON - May, Allyson N. (Allyson Nancy), 1961- author. Link ([S.l.])
1 online resource
Keywords: This volume draws on the recently discovered and extraordinarily rich scrapbook compiled by prosecuting solicitor Francis Hobler about the 1840 murder of Lord William Russell to consider public engagement with the issues raised from discovery of the murder itself through the ensuing legal processes. The murder of Russell by his valet Franois Benjamin Courvoisier was a cause clbre in its own day by virtue of thefact that the victim was a member of one of England's most prominent political families. For criminal justice historians, the significance of this case lies instead in its timing. In 1840, England had neither an official detective force to investigate the murder nor a public prosecutor to undertake the prosecution. Those accused of felony had only recently (1836) won the right to full legal representation, and the conduct of Courvoisier's defence was controversial. Reaction to Courvoisier's execution was also noteworthy, testifying to a new public unease with capital punishment. The subject of master and servant relations in early Victorian England is another key component of the book: previous studies have not considered the murderer's motivation. This book will be of interest to students and scholars of criminal justice and law, Victorian England, and microhistory.